1992
DOI: 10.1097/00000658-199210000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Blood Transfusion and Determinants of Survival After Liver Resection for Metastatic Colorectal Carcinoma

Abstract: The authors reviewed their institutional experience with liver resection for metastatic colorectal carcinoma to (1) determine whether perioperative blood transfusion affects survival; (2) identify prognostic determinants; and (3) estimate the patient requirement for a prospective randomized trial designed to demonstrate efficacy of liver resection. Two hundred eighty consecutive patients treated by potentially curative liver resection between 1960 and 1987 were included. Data were obtained for all but 10 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
218
1
6

Year Published

2001
2001
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 423 publications
(231 citation statements)
references
References 24 publications
6
218
1
6
Order By: Relevance
“…Eighteen of these were single publications (Savage and Malt, 1992;Sugihara et al, 1993; Donato et al, 1994; Doci et al, 1995; Fernandez-Trigo et al, 1995; Fuhrman et al, 1995; Beckurts et al, 1997;Rees et al, 1997; Cady et al, 1998; Ohlsson et al, 1998;Riesener et al, 1998; Bradley et al, 1999; Harmon et al, 1999; Harms et al, 1999; Kemeny et al, 1999a; Bolton and Fuhrman, 2000; Okano et al, 2000; Moroz et al, 2002) and in a further 12 cases the data was obtained from multiple publications (Hughes et al, 1988(Hughes et al, , 1989 Hohenberger et al, 1990 Hohenberger et al, , 1994Scheele et al, 1990Scheele et al, , 1991Scheele et al, , 1995Scheele et al, , 1996Steele Jr et al, 1991Rosen et al, 1992; Gayowski et al, 1994;Stangl et al, 1994; Fong et al, 1995 Fong et al, , 1997 Fong et al, , 1999 Leslie et al, 1995; Jamison et al, 1996 Jamison et al, , 1997 Jenkins et al, 1997; Bakalakos et al, 1998a, b; Iwatsuki et al, 1999; Minagawa et al, 1999; Ambiru et al, 1999a; Kemeny et al, 1999b, c; Brand et al, 2000; DeMatteo et al, 2000; Minagawa et al, 2000). In addition, data on 30-day mortality and morbidity were included from a further nine studies (one with two publications) in which survival data was excluded owing to insufficient or unclear follow up (Minton and Abou-Issa, 1990; Fegiz et al, 1991; Nordlinger et al, 1992;van Ooijen et al, 1992;Wade et al, 1996; Lorenz et al, 1997 Lorenz et al, , 1998; Nadig et al, 1997; Taylor Just two studies included all patients presenting with colorectal liver metastases (Scheele et al, 1990(Scheele et al, , 1991(Scheele et al, , 1995(Scheele et al, , 1996Stangl et al, 1994; Harms et al, 1999) and only three studies presented data on all patients undergoing surgery (radical, nonradical and laparotomy) (Steele Jr et al, 1991 Fuhrman et al, 1995; Bakalakos et al, 1998a).…”
Section: Description Of Studies Identifiedmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighteen of these were single publications (Savage and Malt, 1992;Sugihara et al, 1993; Donato et al, 1994; Doci et al, 1995; Fernandez-Trigo et al, 1995; Fuhrman et al, 1995; Beckurts et al, 1997;Rees et al, 1997; Cady et al, 1998; Ohlsson et al, 1998;Riesener et al, 1998; Bradley et al, 1999; Harmon et al, 1999; Harms et al, 1999; Kemeny et al, 1999a; Bolton and Fuhrman, 2000; Okano et al, 2000; Moroz et al, 2002) and in a further 12 cases the data was obtained from multiple publications (Hughes et al, 1988(Hughes et al, , 1989 Hohenberger et al, 1990 Hohenberger et al, , 1994Scheele et al, 1990Scheele et al, , 1991Scheele et al, , 1995Scheele et al, , 1996Steele Jr et al, 1991Rosen et al, 1992; Gayowski et al, 1994;Stangl et al, 1994; Fong et al, 1995 Fong et al, , 1997 Fong et al, , 1999 Leslie et al, 1995; Jamison et al, 1996 Jamison et al, , 1997 Jenkins et al, 1997; Bakalakos et al, 1998a, b; Iwatsuki et al, 1999; Minagawa et al, 1999; Ambiru et al, 1999a; Kemeny et al, 1999b, c; Brand et al, 2000; DeMatteo et al, 2000; Minagawa et al, 2000). In addition, data on 30-day mortality and morbidity were included from a further nine studies (one with two publications) in which survival data was excluded owing to insufficient or unclear follow up (Minton and Abou-Issa, 1990; Fegiz et al, 1991; Nordlinger et al, 1992;van Ooijen et al, 1992;Wade et al, 1996; Lorenz et al, 1997 Lorenz et al, , 1998; Nadig et al, 1997; Taylor Just two studies included all patients presenting with colorectal liver metastases (Scheele et al, 1990(Scheele et al, , 1991(Scheele et al, , 1995(Scheele et al, , 1996Stangl et al, 1994; Harms et al, 1999) and only three studies presented data on all patients undergoing surgery (radical, nonradical and laparotomy) (Steele Jr et al, 1991 Fuhrman et al, 1995; Bakalakos et al, 1998a).…”
Section: Description Of Studies Identifiedmentioning
confidence: 99%
“…Eighteen of these were single publications (Savage and Malt, 1992;Sugihara et al, 1993;Donato et al, 1994;Doci et al, 1995;Fernandez-Trigo et al, 1995;Fuhrman et al, 1995;Beckurts et al, 1997;Rees et al, 1997;Cady et al, 1998;Ohlsson et al, 1998;Riesener et al, 1998;Bradley et al, 1999;Harmon et al, 1999;Harms et al, 1999;Kemeny et al, 1999a;Bolton and Fuhrman, 2000;Okano et al, 2000;Moroz et al, 2002) and in a further 12 cases the data was obtained from multiple publications (Hughes et al, 1988(Hughes et al, , 1989Hohenberger et al, 1990Hohenberger et al, , 1994Scheele et al, 1990Scheele et al, , 1991Scheele et al, , 1995Scheele et al, , 1996Steele Jr et al, 1991Rosen et al, 1992;Gayowski et al, 1994;Stangl et al, 1994;Fong et al, 1995Fong et al, , 1997Fong et al, , 1999Leslie et al, 1995;Jamison et al, 1996Jamison et al, , 1997Jenkins et al, 1997;Bakalakos et al, 1998a, b;Iwatsuki et al, 1999;Minagawa et al, 1999;Ambiru et al, 1999a;Kemeny et al, 1999b, c;Brand et al, 2000;DeMatteo et al, 2000;Minagawa et al, 2000). In addition, data on 30-day mortality and morbidity were included from a further nine s...…”
Section: Description Of Studies Identifiedmentioning
confidence: 99%
“…The intrahepatic tumour number as an exclusion criterion for liver surgery is still a matter of debate. Several investigators regard three tumours as an upper limit when liver resection is to be performed (61,62,64,66), while in other studies the tumour number has not been found to be a significant prognostic factor (59,60,63,65,67). It is estimated that 10 Á/20% of all patients with colorectal liver metastases are candidates for liver surgery (76).…”
Section: Resection Of Recurrencementioning
confidence: 99%
“…Atualmente, com uma seleção adequada dos pacientes, a ressecção hepática é o tratamento de escolha para metástases de câncer colorretal conf inadas ao fígado e resulta em sobrevida que varia de 25% a 40% em várias séries (1,13,19,20,34,37) . Ocasionalmente, a ressecção total de doença metastática extra-hepática intra-abdominal combinada com a ressecção hepática e mesmo a ressecção de metástases pulmonares, tem se justificado com aumento da sobrevida (20,25) .…”
Section: Introductionunclassified
“…Os pacientes com metástases hepáticas de câncer colorretal representam um grupo de comportamento biológico exclusivo visto que outros tumores do trato gastrointestinal, quando metastáticos no fígado, não apresentam padrões de resposta favorável com a ressecção (7) . Vários estudos têm sido realizados na tentativa de definir fatores prognósticos quanto à recidiva dessas lesões no fígado, na sobrevida e eventual cura dos pacientes operados (1,13,19,20,24,29,31,34,37,39) . A análise de fatores prognósticos pode ser útil para selecionar pacientes para a ressecção hepática, delinear grupos de risco, estimar o tempo de sobrevida e oferecer aos pacientes dados objetivos sobre o seu prognóstico (39) .…”
Section: Introductionunclassified